Upaya Meningkatkan Hasil Belajar Peserta Didik Menggunakan Multimedia pada Mata Pelajaran Menggunakan Perkakas Tangan Kelas X Teknik Fabrikasi Logam Di Smk Negeri 2 Karang Baru - Aiyub (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2022)
This study uses multimedia as a learning medium to determine the increase in learning outcomes for Class X students of Metal Fabrication Techniques in subjects using hand tools at SMK Negeri 2 Karang Baru. The research used in this research is Classroom Action Research (CAR) with two cycles. From the results of the study it can be seen that there was an increase in student learning outcomes, in the pre-test results the average value obtained by students was 54.51 and the percentage of graduation rates based on the Graduate Competency Standards (SKL) was 35.48%, in the first cycle the average value obtained by students was 71.12 and the percentage of graduation based on the Graduation Competency Standards (SKL) was 74.19%, in the second cycle the average value obtained by students was 73.22 and the percentage of graduation based on the Graduation Competency Standards (SKL) was 87.09% . In this case the use of multimedia in subjects using hand tools increased the learning outcomes of Class X Metal Fabrication Engineering students, totaling 31 students. In the learning outcomes in the initial action by evaluating learning outcomes through giving a pre-test, the Graduation Percentage on learning outcomes in cycle I obtained a satisfactory increase, in the initial conditions the graduation percentage results were obtained 35.48% while in cycle I learning outcomes the graduation percentage results were obtained 74 .19% means that there is an increase in student learning outcomes in the subject of Using Hand Tools using Multimedia 38.71%. The results of increasing student learning outcomes were achieved by using Multimedia as a learning tool in the Subject Using Hand Tools in Class X Metal Fabrication Engineering.